Reassessing the role of magnetite during natural hydrogen generation - Geymond, Ugo; Briolet, Théo; Combaudon, Valentine; Sissmann, Olivier; Martinez, Isabelle; Duttine, Mathieu; Moretti, Isabelle (Frontiers in Earth Science, 2023)
Interactions between water and ferrous rocks are known to generate natural H2 in oceanic and continental domains via the oxidation of iron. Such generation has been mainly investigated through the alteration of Fe2+-silicate and some Fe2+-carbonates. So far, magnetite (α-Fe3O4) has never been considered as a potential source mineral for natural H2 since it is considered as a by-product of every known chemical reaction leading to the formation of H2, despite it bears 1/3 of Fe2+ in its mineral lattice. This iron oxide is rather seen as a good catalyst for the formation of H2. Recently, hydrogen emissions were observed in the surroundings of banded iron formations (BIF) that are constituted of, among other minerals, magnetite. Thus, this work is an attempt to constrain the true potential of magnetite by means of batch reactor experiments and additional thermodynamic calculations. It explores theoretical and experimental reaction pathways of magnetite during water-rock interactions, focusing on low temperatures (T < 200°C). For the purpose of the experiments, gold capsules filled with magnetite powders were run at 80°C and 200°C. Gas products were analyzed using gas chromatography (GC) while solid products were characterized by X-ray diffraction (XRD), Mössbauer spectroscopy, and scanning electron microscopy (SEM). After experimental alteration, high amounts of H2 were quantified while mineralogical transitions were observed by SEM. It showed self-reorganization of the primary iron oxide resulting in sharp-edge and better crystalized secondary minerals. In parallel, XRD analyses showed tiny changes between the patterns of the initial powder and the solid products of reaction. Finally, Mössbauer spectroscopy revealed that the starting magnetite was partly converted to maghemite (γ-Fe2O3), a metastable Fe-oxide only containing Fe3+. Major implications arise from these results. Concerning H2 exploration, this work provides evidence that natural hydrogen can be generated at near-ambient temperature. It also infers that magnetite-rich lithologies such as BIF should be targeted while looking for H2 source rocks. In addition, these outcomes could be of major interest for mining companies as they provide key elements to understand the formation of BIF-hosted iron ores.